(untitled) (Research, Society and Development, 2022)
The meniscal ossicle is considered a rare condition and its etiology are very controversial. Clinically, the ossicle may be associated with pain and a feeling of blockage in the movement of patients, but it is also described as asymptomatic and incidental during arthroscopy. When the presence of a bone structure within the knee joint is identified on plain radiographs, MRI can be used to differentiate between a meniscal ossicle and a loose body. The vast majority of ossicles, about 89% are located in the medial meniscus and 95% were located in the posterior horn or root of the meniscus.5 Thus, the present study aimed to describe the case of a 63-year-old woman with chronic pain diffuse in the right knee for 5 months with difficulty in carrying out his daily activities where a meniscal ossicle was identified in MRI in the coronal section in the T1 in A sequence and in the axial section in the DP SPIR sequences. Our objective is to report a case of double meniscal ossicle diagnosed by MRI.